Shaping the Concept of Mage Through Image Schemas in Dragon Age Origins - DEAN RAIYASMI; ELVI CITRARESMANA (English Journal Literacy Utama, 2019)
Language shapes the human mind and its concept toward things. Using image schemas, in nowadays technology, even AI (artificial intelligence) can concept things in response to their creator negativity or positivity. This is reflected in one of the most selling games around the world in 2012 called Dragon Age